Influence of Cavity Width on Attenuation Characteristic of Gas Explosion Wave. (26th February 2021) - Xu, Dengke; Mu, Chaomin; Li, Zhongqing; Zhang, Wenqing
Abstract : This study aimed to investigate the influence of cavity width on the attenuation characteristic of gas explosion wave. Attenuation mechanism of gas explosion wave through cavity was obtained by numerical simulation. The gas explosion shock wave energy can be greatly attenuated through the cavity structure in five stages, namely, plane wave, expansion, oblique reflection, Mach reflection, and reflection stack, to ensure that it is eliminated. Cavities with various width sizes, namely, 500 ∗ 300 ∗ 200, 500 ∗ 500 ∗ 200, and 500 ∗ 800 ∗ 200 (length ∗ width ∗ height, unit: mm), were experimented to further investigate the attenuation characteristics through a self-established large-size pipe gas explosion experimental system with 200 mm diameter and 36 m length. Results showed an evident attenuation effect on flame duration light intensity (FDLI) and peak overpressure with increasing cavity width. Compared with 300 mm, the overall FDLI decreased by 83.0%, and the peak overpressure decreased by 71.2% when the cavity width was 800 mm. The fitting curves of the FDLI and peak overpressure attenuation factors to width-diameter demonstrated that the critical width-diameter was 2.19 when the FDLI attenuation factor was 1. The FDLI attenuation factor sharply decreased at the width-diameter ratio range from 1.5 to 2.5 and basically remained steady at 0.17 at the width-diameter ratio range from 2.7 to 4.0. The peak overpressure attenuation factor gradually decreased with the increase of width-diameter ratio and changed from 0.93 to 0.28 with width-diameter ratio from 1.5 to 4.0. The research results can serve as a good reference for the design of gas explosion wave-absorbing structures.